Progesterone as a neuroprotectant in stroke - Wong, Raymond (2013)
Progesterone has been shown to be neuroprotective in a number of central nervous system injury models, including cerebral ischaemia. There is still a lack of understanding behind progesterone’s neuropotective properties, and the purpose of this project is to clarify some of these issues. Osmotic mini-pump infusion was hypothesised to more effective in delivering progesterone to the target organ of the brain, when compared to a bolus intraperitoneal injection. Progesterone pharmacokinetic profiles were compared between different dosing regimes. Intraperitoneal progesterone injection had a short half-life in both plasma and brain, while osmotic mini-pumps delivered higher concentrations of progesterone in plasma and particularly in brain, over a longer period, which supports the hypothesis.